Call warrants pricing formula under mixed-fractional Brownian motion with Merton jump-diffusion - S. N. I., Ibrahim; M. F., Laham (Lviv Polytechnic National University, 2022)
Mixed fractional Brownian motion (MFBM) is a linear combination of a Brownian motion and an independent fractional Brownian motion which may overcome the problem of arbitrage, while a jump process in time series is another problem to be address in modeling stock prices. This study models call warrants with MFBM and includes the jump process in its dynamics. The pricing formula for a warrant with mixed-fractional Brownian motion and jump, is obtained via quasi-conditional expectation and risk-neutral valuation.